ANALISIS KETERSEDIAAN BAHAN BAKU DAN NILAI TAMBAH PRODUK MANISAN PADA AGROINDUSTRI REZEKI MORO DI DESA PESUCEN KECAMATAN KALIPURO KABUPATEN BANYUWANGI - Inkatama Kharismawanti; Djoko Soejono (Universitas Sebelas Maret, 2019)
Candied fruit is one of the processed foods which favored by many people. One of the sweets agro-industry that exists in Pesucen, Kalipuro, Banyuwangi is Rezeki Moro agro-industry. This study aimed to find out: 1) the stock level of raw materials of candid fruit in Rezeki Moro agro-industry, 2) the optimal time to reorder raw materials, and 3) the amount of added value of fruit after being processed into candied fruit. The data analysis used was the analysis of raw materials availability using EOQ and ROP methods and value-added. The result of the study showed that the need for raw material such as nutmeg was 30 kilograms, while the number of economical orders with the EOQ method was 73 kilograms. The need for tamarind was 25 kilograms, while the number of economical orders with the EOQ method was 32 kilograms, also the need for ceremai (Phyllantus acidus) was 50 kilograms while the number of economical orders with the EOQ method was 60 kilograms. The level of reordering of raw materials from all sweets product in Rezeki Moro agro-industry was efficient since the ROP point was smaller than the EOQ point. The processing of candied nutmeg provided an added value of Rp. 9,848.00 (39.39%). The added value of processing candied tamarind is Rp. 17,468.00 (46%). Furthermore, the processing of candied ceremai has added value Rp. 12,548.00 with a value-added ratio of 43.5%.